New LHCb pentaquarks as hadrocharmonium states - Eides, Michael I.; Petrov, Victor Yu; Polyakov, Maxim V. (Modern physics letters A, 2020)
New LHCb Collaboration results on pentaquarks with hidden charm1 are discussed. These results fit nicely in the hadrocharmonium pentaquark scenario. 2 , 3 , In the new data the old LHCb pentaquark P c ( 4 4 5 0 ) splits into two states P c ( 4 4 4 0 ) and P c ( 4 4 5 7 ) . We interpret these two almost degenerated hadrocharmonium states with J P = 1 / 2 − and J P = 3 / 2 − , as a result of hyperfine splitting between hadrocharmonium states predicted in Ref. 2. It arises due to QCD multipole interaction between color-singlet hadrocharmonium constituents. We improve the theoretical estimate of hyperfine splitting 2 , 3 that is compatible with the experimental data. The new P c ( 4 3 1 2 ) state finds a natural explanation as a bound state of χ c 0 and a nucleon, with I = 1 / 2 , J P = 1 / 2 + and binding energy 42 MeV. As a bound state of a spin- 0 meson and a nucleon, hadrocharmonium pentaquark P c ( 4 3 1 2 ) does not experience hyperfine splitting. We find a series of hadrocharmonium states in the vicinity of the wide P c ( 4 3 8 0 ) pentaquark that can explain its apparently large decay width. We compare the hadrocharmonium and molecular pentaquark scenarios and discuss their relative advantages and drawbacks.